Developing intercultural competence in college business English students: A study of innovative teaching in China. (January 2023) - Mu, Yuting; Yu, Baohua
Abstract: Despite the increasing need to develop students' intercultural competence in China, the relationship between the approaches used to teach the English language and the cultivation of students' intercultural competence remains largely under-researched. Based on Byram's intercultural model and the intercultural language teaching framework, using action research we developed and implemented new teaching approaches to cultivate intercultural competence among students using a quasi-experimental design that combined qualitative and quantitative methods. Two classes of undergraduate students majoring in Business English were randomly selected, with one being assigned as the treatment group (n = 33) and the other as the control group (n = 32). The primary data consisted of questionnaires, journals, and interviews. After participating in a three-month intercultural speaking course where the treatment group students were guided through an intercultural learning process of noticing, comparing, and reflecting, findings revealed that they developed intercultural competence regarding their attitudes, knowledge, skills, and awareness. Implications for facilitating students' intercultural competence are discussed.